2018
DOI: 10.4081/monaldi.2018.976
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone treatment in chronic heart failure. Review of literature and future perspectives

Abstract: Mounting evidence suggests that hormonal deficiencies (HD) have an important role in chronic heart failure (CHF). In particular, androgen depletion is common in men with CHF and is associated with increased morbidity and mortality. This review summarizes the current understanding of the complex relationship between CHF and testosterone, focusing on evidence derived from clinical trials that have investigated the role of testosterone in the treatment of CHF. A greater comprehension of this area will allow resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…8 Despite these findings, concerns about slow recruitment in this trial have tempered enthusiasm for coenzyme Q10 supplementation in clinical practice. 9,31 Hormonal therapies have been proposed for the treatment of HF, but trials have shown a neutral effect of testosterone, 40,41 growth hormone, 30,42 and thyroid hormone 43–45 in HF outcomes. Nondihydropyridine calcium channel blockers—diltiazem and verapamil—are myocardial depressants and generally not well tolerated in HF. Verapamil had no impact of survival or major cardiac events post-MI, including in those patients with HFrEF after acute MI.…”
Section: Stage C Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Despite these findings, concerns about slow recruitment in this trial have tempered enthusiasm for coenzyme Q10 supplementation in clinical practice. 9,31 Hormonal therapies have been proposed for the treatment of HF, but trials have shown a neutral effect of testosterone, 40,41 growth hormone, 30,42 and thyroid hormone 43–45 in HF outcomes. Nondihydropyridine calcium channel blockers—diltiazem and verapamil—are myocardial depressants and generally not well tolerated in HF. Verapamil had no impact of survival or major cardiac events post-MI, including in those patients with HFrEF after acute MI.…”
Section: Stage C Hfmentioning
confidence: 99%
“…8 Despite these findings, concerns about slow recruitment in this trial have tempered enthusiasm for coenzyme Q10 supplementation in clinical practice. 9,31 Hormonal therapies have been proposed for the treatment of HF, but trials have shown a neutral effect of testosterone, 40,41 growth hormone, 30,42 and thyroid hormone 43–45 in HF outcomes.…”
Section: Stage C Hfmentioning
confidence: 99%
“…Testosterone deficiency represents a fundamental element in the pathophysiology of chronic heart failure, resulting in a reduction of muscle mass, impaired use of energy, dyspnea and fatigue (26,27). Lower plasma levels of total testosterone and DHEA-S were associated with an increased risk of incident HF, both in HFpEF and HFrEF (28), suggesting a possible use in community-based screening programs.…”
Section: Dehydroepiandrosterone-sulfate (Dhea-s) and Testosteronementioning
confidence: 99%
“…Testosterone deficiency has been related with the severity of cardiac dysfunction and poor prognosis in CHF patients (10,11). Accordingly, randomized controlled trials (RCTs) have been performed to evaluate the efficacy of testosterone supplementation in CHF patients (11)(12)(13). However, the results of the RCTs were not always consistent (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%